Pemanfaatan Daun Serai Wangi sebagai Bahan Baku Pembuatan Minyak Atsiri untuk Peningkatan Ekonomi Masyarakat Desa - Muhammad Afdhol; Marliati Ahmad; Fiki Hidayat; Tomi Erfando; Fitra Lestari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The fall in prices of oil palm and rubber has an impact on weakening the economy of the community, so we need another solution in an effort to increase again. Lemongrass plant is one of the producers of essential oils. Essential oils are plant extracts that are widely used in the chemical industry. Lemongrass plants suitable for planting in tropical climates and do not require expensive maintenance and a long time. The production of essential oils through the distillation process so that condensate is produced which will be purified through the distillation process. Lemongrass oil commodity has a high selling price, so it is expected to increase farmers' income and employment. The results of this community service were that the Batubelah Village Community was interested in citronella cultivation considering the economic condition of the community had plummeted due to falling oil and rubber prices.